Risk Assessment on The Bandung Hilton Hotel Construction Project Utilizing The FMEA and FTA Methods - Kholida, Lily; Melina Lubis, Nadia Tutur; Citra, Zel; Hasdian, Elhazri (CIVED, 2024)
Risk is the possibility or uncertainty of unexpected events occurring during the implementation of work which could harm the party carrying out the activity, the example is a risk of work accidents. The potential risk of work accidents also occurs in the Hilton Hotel Construction Project in Kota Baru Parahyangan - West Bandung. The project is a high-rise building with a height of 23 floors which of course has a fairly high risk of work accidents. This research aims to find out the dominant risk and its factors.This research applied two methods in analyzing, those methods are Failure Mode and Effect Analysis Method (FMEA) and Fault Tree Analysis Method (FTA). Having can be identified and analyzed that risks by using those methods, this research did some steps by using Method for Obtain Cut Set (MOCUS) for finding basic event combination.The results of this research are to determine the dominant risk of work accidents using the FMEA method, namely the activity of workers falling from a height during glass installation work with an RPN value of 26,3. Based on the FTA method, it produces 16 basic events are feeling unwell, lack of concentration, lack of enthusiasm for work, excessive joking, not seeing signs, lack of communication, lack of supervision time, lack of K3 training, less comfortable using PPE, limited amount of PPE, lack of training, lack of experience, signs that are too small, signs blocked by objects, slippery roads due to rain, and a messy work environment.